Voice Hygiene - Begović, Amadea (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter discusses the role of vocal hygiene in maintaining a healthy voice, which is particularly important for individuals who use their voice intensively in their professions, such as teachers, doctors, and other professionals. Vocal hygiene involves the proper use and care of the voice to prevent voice-related issues, injuries, or illnesses. The chapter also provides an explanation of sound production and the functioning of the vocal cords. Preventive measures such as adequate hydration, regular vocal breaks, breathing and vocal exercises, and avoiding rapid and loud speech are emphasized as essential aspects of vocal hygiene. Studies show that knowledge of vocal hygiene reduces the risk of voice problems, highlighting the importance of integrating vocal hygiene education into educational institutions. Such initiatives could enhance both professional efficiency and vocal health.